IMPLEMENTASI HUBUNGAN MASYARAKAT (HUMAS) UNTUK MENINGKATKAN PELAYANAN DI SEKOLAH SMA SWASTA ESA PRAKARSA SELESAI - Ade Khairida; Khairida, Ade; Fachrurrowzi, Lendra; Sanjani, Maulana Akbar (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2024)
This research was conducted due to a significant gap in studies discussing the concrete implementation of public relations to improve the quality of educational services, where most studies focus on the marketing and promotional aspects of schools rather than the direct, ongoing application to pedagogical quality, technology integration, and crisis response in the digital era. This research was conducted to address the need to improve the quality of school services through the strategic role of public relations (PR). The main objective of this study is to analyze how public relations planning, implementation, and evaluation are applied to improve the quality of services at Esa Prakarsa Sempurna Private High School. This study uses a qualitative method with a descriptive approach, through interviews, observation, and documentation as data collection techniques. The results show that school public relations plays a crucial role in building effective communication with stakeholders through social media, the school website, periodic bulletins, and student achievement publications. A structured public relations strategy and information digitalization improve the school's image and facilitate public access to information on educational services. The conclusion of this study is that the implementation of planned, adaptive, and communicative public relations has been proven to improve the quality of school services, strengthen public trust, and build positive relationships between schools and the community.